2021
DOI: 10.1177/10731911211063229
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Emotion Regulation Skill Use During Treatment: A Promising Methodological Approach

Abstract: Emotion regulation has become ubiquitous in the study of psychopathology and a growing number of treatment outcome studies are collecting data on emotion regulation skill use. However, traditional measures of emotion regulation fail to capture important nuances in emotion regulation processes, their relationship to psychopathology, and how individuals use emotion regulation skills over time and across contexts. Novel methodologies are particularly needed for measuring emotion regulation in the context of treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 71 publications
0
2
0
Order By: Relevance
“…Although there is some overlap in the constructs of maladaptive and adaptive coping with the clinical outcomes measured here (e.g., the maladaptive strategy "got mad at the people or things that caused the problem" and the interpersonal item "I lose my temper too easily"), the outcomes measured here tend to reflect beliefs about oneself (e.g., "My feelings of distress are not acceptable"), one's capacities (e.g., "When I'm upset, I have difficulty getting work done") or behaviors that are distinct from adaptive or maladaptive coping (e.g., "I break or spill things because of carelessness"). Future researchers are encouraged to collect more intensive data using measures of strategy use and distinct clinical outcomes (e.g., depression, attachment, functioning) in larger samples to provide a more powerful test of these interpretations (Nauphal et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Although there is some overlap in the constructs of maladaptive and adaptive coping with the clinical outcomes measured here (e.g., the maladaptive strategy "got mad at the people or things that caused the problem" and the interpersonal item "I lose my temper too easily"), the outcomes measured here tend to reflect beliefs about oneself (e.g., "My feelings of distress are not acceptable"), one's capacities (e.g., "When I'm upset, I have difficulty getting work done") or behaviors that are distinct from adaptive or maladaptive coping (e.g., "I break or spill things because of carelessness"). Future researchers are encouraged to collect more intensive data using measures of strategy use and distinct clinical outcomes (e.g., depression, attachment, functioning) in larger samples to provide a more powerful test of these interpretations (Nauphal et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Research has also shown modest correlations between ER measured as a trait compared to momentary assessments of ER (38)(39). Regarding intervention research, the sole use of pre-and post-assessments of ER limits researchers from determining when, how, and in response to which elements change occurs (40). With daily measurements of ER, we can investigate ER as a dynamic process in relation to the intervention and the mechanisms that lead to improved mental health and well-being (33).…”
Section: Co-design For Implementability In Natural Practicementioning
confidence: 99%